Faktor-faktor yang Memengaruhi Kelancaran Pengembalian Kredit Usaha Rakyat (KUR) yang Disalurkan PT Bank Negara Indonesia (Persero) Tbk: Factors Influencing Repayment of People's Business Credits (Kur) Distributed By PT Bank Negara Indonesia (Persero) Tbk Small Credit Center Bogor - Putra, Rahmadiansyah Putra; Rifin, Amzul; Saptono, Imam Teguh (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The role of PT Bank Negara Indonesia (Persero) Tbk (BNI)is essential in distributing People's Business Credits (KUR) to support micro and small businesses in Indonesia. BNI needs to mitigate credit risk to ensure KUR scheme's sustainability and maintain profitability. The objectives of this study are 1) To analyze the development of Non-Performing Loan (NPLs) from KUR distributed by BNI SKC Bogor, and 2) To analyze the factors that influence repayment of KUR distributed by BNI SKC Bogor. This study used secondary data from 1.031 KUR borrowers in 2019. The study results show that KUR distribution by BNI SKC Bogor from 2017-2019 grew by 16.47%. However, credit risk increased where NPL grew 117 % from 0.798% in 2017 to 1.18% in 2019. Model Logit shows that credit characteristics (total credit and interest rates), business characteristics (Dummy service sector and income), and individual characteristics (age) affect the repayment of KUR. The managerial implications for BNI SKC Bogor are: 1) To increase credit distribution in the productive sector (services), (2) to Additional collateral before credit distribution, and 3) Mitigation credit risks towards younger debtors, middle-income borrowers (Rp 10-20 millions/month), and higher interest rate borrower. Keywords: non performing loan, logit, people business credit (KUR), Mitigation risks, BNI